The Palm at the End of the Mind : Relatedness, Religiosity, and the Real - Jackson, Michael, 1940- (Book collections on Project MUSE., 2009)
A meditation on "border situations," such as birth, death, and crisis, where boundaries between cultures and individuals become blurred.